The Influence of Utilizing Accounting Information Systems On Managerial Performance at BPJS Kesehatan Bandar Lampung Branch Office - Aulia Gusmiarni; Sudrajat Sudrajat (Lembaga Riset dan Inovasi Al-Matani, 2023)
High inflation in Lampung Province in the second quarter of 2022 had an impact on people's lives. This affects the priority scale of needs that must be met by the community. The Bandar Lampung BPJS Kesehatan subsidiary is one of the affected organizations. Based on the December 2022 target achievement report, it was announced that the achievement of interests was below the previously set target. As operational actors, employees play an important role in achieving goals. Having an optimal accounting information system can produce good productivity. This research was conducted at the BPJS Kesehatan Bandar Lampung branch. The method of determining the research sample is based on saturated sampling technique, where the sample is 83 employees. The questionnaire is used as a research tool, by utilizing data analysis techniques such as data quality testing, statistical testing, and hypothesis testing. The results showed that the use of accounting information systems had a positive effect on improving the management efficiency of BPJS Kesehatan employees in the Bandar Lampung branch.